Effects of future climate change on the geographical distribution of a bird endemic to South American floodplains - Zucchetto, Mayara F.; Da Silveira, Natalia S. [UNESP]; Prasniewski, Victor M.; Arnhold, Tatiane; Sobral-Souza, Thadeu; De Pinho, João B. (Resilience Alliance, 2021)
Future climate change poses an immediate threat to biodiversity. Species are shifting their geographic distribution in direct response to climate change. Species around the globe are expected to redistribute poleward and/or to high elevations. However, in the Neotropical region, the effects of climate change on species distribution are still unclear. Here, we aimed to infer the current and future geographical distribution of an insectivorous bird species endemic to South American floodplains, the Mato Grosso Antbird (Cercomacra melanaria). We also estimated shifts in the variables of elevation, longitude, latitude, and slope based on forecasting. Current and future distribution in different climate scenarios were predicted using ecological niche modeling (ENM). A non-parametric Kruskall-Wallis test followed by Dunn’s post hoc test were carried out to determine if dependent variables (elevation, slope, latitude, and longitude) differed between climate scenarios. Our findings suggest that future climate change will have negative effects (range contraction) on the distribution of the Mato Grosso Antbird. The decrease in the species’ geographical range will cause it to shift to higher elevations, latitudes, longitudes, and slopes. The species should tend to disperse toward more suitable areas located in highlands close to wetlands, such as the headwaters of the Upper Paraguay River Basin (UPB), and toward the Andean highlands. However, this species inhabits strictly forested environments covering a small home range and its mobility capacity is limited. It is possible that the species will not be able to achieve future geographical redistribution, thus increasing its risk of extinction.
Effets des futurs changements climatiques sur la répartition géographique d'un oiseau endémique des plaines inondables d'Amérique du Sud
Keywords: Cercomacra melanaria; Mato Grosso Antbird; Niche modeling; Pantanal; Thamnophilidae; Wetland